The impact of energy transition on distribution network costs and effectiveness of yardstick competition: an empirical analysis for the Netherlands - van Montfoort, Floris; Dijkstra, Peter T.; Mulder, Machiel (Journal of regulatory economics, 2024)
We assess the impact of regional differences related to energy transition on average costs and allowed revenues for a panel of Dutch electricity distribution system operators (DSOs) subject to yardstick competition. Yardstick competition entails that the allowed revenues of DSOs are based on the average costs of the entire industry, which requires that these DSOs are comparable. This comparability requirement is challenged by the penetration of distributed generation and other distributed energy resources, which may cause regional differences among DSOs. Estimating an average-cost function for the entire population of Dutch DSOs for the period 2012–2020, we find that the installed capacity of solar PV, installed capacity of on-shore wind and number of public electric-vehicle charging points have a significant effect on unit costs of DSOs. If yardstick competition does not take these effects into account, the allowed revenues for some DSOs (having above-average shares of energy-transition variables) are too low, whereas allowed revenues for other DSOs (having below-average shares of energy-transition variables) are too high. We find that taking the impact into account can change the price caps of individual DSOs with a percentage up to around 20%.